Vegetation response to forest ditch reconstruction: Promoting a potential habitat for insect-pollinated plant species? - Gerra-Inohosa, Linda; Lībiete, Zane; Matisone, Ilze (Metsanduslikud uurimused, 2023)
In a managed forest landscape, the high degree of human intervention has caused significant shifts in natural processes, and preservation of remaining natural ecosystem features is crucial to safeguard ecosystem functioning and support ecosystem services. While drainage ditches, subject to regular maintenance, are anthropogenically created and maintained infrastructure elements, they may still support diverse environmental conditions and provide habitats for a variety of plant species, including flowering plants important for pollinators. We assessed vegetation composition changes on recently reconstructed and unmanaged forest ditches and ditch edges in a commercial forest in Central Latvia in two surveys (one and five years after the ditch reconstruction). We used generalized linear mixed-effects models to analyze the impact of environmental variables on species richness and detrended correspondence analysis to analyze plant species composition. We found higher total plant species richness and insect-pollinated plant species richness along recently reconstructed ditches. The differences were mainly explained by better light availability beside reconstructed ditches. Anthropogenically created and managed ecosystems may support biodiversity and directly and indirectly contribute to the provision of different ecosystem services, including pollination.